The Research Institute for Olympic Sports (KIHU)
The Research Institute for Olympic Sports (KIHU) was established in the spring of 1991 as an independent unit of the Foundation for Sport and Health Sciences and is supported by the University of Jyväskylä, the Finnish Ministry of Education and the Finnish Olympic Committee. KIHU`s role is to conduct research in Olympic sports and to apply research results to coaching and training. KIHU`s mission is to secure the future of Olympic sports in Finland. Operations at KIHU began on January 1, 1991 with the help of a grant from state-sanctioned gambling funds. Four senior and two junior researchers, three research assistants and four other employees were hired. With the help of other funding, the number of employees has increased. The basis of operations at KIHU is in applied research and in the dissemination of information. Research projects are funded by the Ministry of Education, the Olympic Committee, sport federations and KIHU`s own funds. The projects are carried out in cooperation with sport federations, training centers and private companies. KIHU is also an expert organization whose services are used for training and consulting. International information exchange during congresses and joint projects has a significant role in KIHU`s operations. You also find an overview of the projects conducted at KIHU in this internetsite.